2012
DOI: 10.1371/journal.pone.0028238
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Acceptance of Oral and Parenteral HIV Preexposure Prophylaxis among Potential User Groups: A Multinational Study

Abstract: BackgroundThe use of antiviral medications by HIV negative people to prevent acquisition of HIV or pre-exposure prophylaxis (PrEP) has shown promising results in recent trials. To understand the potential impact of PrEP for HIV prevention, in addition to efficacy data, we need to understand both the acceptability of PrEP among members of potential user groups and the factors likely to determine uptake.Methods and findingsSurveys of willingness to use PrEP products were conducted with 1,790 members of potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
211
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(229 citation statements)
references
References 37 publications
15
211
3
Order By: Relevance
“…Although several studies are emerging with regard to the acceptability of oral PrEP in different populations, [14][15][16][17][18] to our knowledge, this is the first to assess the acceptability of oral versus rectal PrEP among MSM and TGW who mainly practice URAI. Importantly, data for this study were collected in 2008, before the results of the iPrEx study were disseminated in 2010, 2 thereby providing a unique opportunity to assess the potential PrEP acceptability when the approach was still hypothetical.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies are emerging with regard to the acceptability of oral PrEP in different populations, [14][15][16][17][18] to our knowledge, this is the first to assess the acceptability of oral versus rectal PrEP among MSM and TGW who mainly practice URAI. Importantly, data for this study were collected in 2008, before the results of the iPrEx study were disseminated in 2010, 2 thereby providing a unique opportunity to assess the potential PrEP acceptability when the approach was still hypothetical.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have assessed PrEP acceptability among men who have sex with men, 21,22 men and women in international settings, [23][24][25][26] and high risk heterosexuals in the US, 27,28 there is a critical need to understand PrEP acceptability and product preferences among US black women, [29][30][31][32] given the high HIV incidence in this population. A national survey of adult women in the US found that African American women were more likely than white women to consider using oral PrEP and that cost, peer perspectives, and physician input would influence their decision making.…”
mentioning
confidence: 99%
“…Abs are generally well tolerated and can be administered infrequently because of their longer half-life in vivo. Indeed, a recent multinational study of potential PrEP users showed that route of administration was the most important attribute regarding acceptability of a PrEP program, with a monthly or bimonthly injection preferred over daily or intermittent pills (17). In addition, numerous studies in macaques have demonstrated that passive immunization with bNAbs can prevent infection by hybrid simian-human immunodeficiency viruses (18)(19)(20)(21).…”
mentioning
confidence: 99%